CHARACTERISTICS OF NURSING PROFESSIONALS AT NERS STUDY STUDENTS OF HEALTH FACULTY, MUHAMMADIYAH UNIVERSITY, SEMARANG - Tri Hartiti; Diah Wulandari (NURSCOPE: Jurnal Penelitian dan Pemikiran Ilmiah Keperawatan, 2018)
Background: Nursing professionalvalueis a foundation for a nurse in nursing practicing which can described by three valuecomponents, those are caring, activism, and professionalism. Applying nursing professional valuestarted by when the education process until practice in the clinic. The purpose of the research: Knowing describe of nursing professional value on student of program study nursing profession Faculty of Nursing and Health University of Muhammadiyah Semarang.Researchmethods: Kind of this study was descriptive qualitative which is applied survey approach, applied total sampling method with total respondent were 114 students, the data submitted was applied questionnaire of NPSV-3 (Nurse Professional Values Scale-3) consists of 28 question with Likert scale (Weish & Schank, 2017). Statistic analysis applied univariat analysis. Research results: The research showed characteristic of female sample 70 (61,4%), respondent age minimum 22 years and maximum 30 years. The value of nursing professionals with the category of less good 2 (1.8%), both 112 (98.2%). Caringvalue with category less good 1 (9%), good 113 (99,1%). The value of activismwith category less good 4 (3.5%), good 110 (96,5%). The value of professionalismwith the less good category 1 (9%), either 113 (99.1%).Conclusion: It was concluded that the average of the three components of the overall score in both categories with the total value of professional nursing was 112 (98.2%) with good category.Suggestion: This study canbe the evaluation material for institution of education and student nurse in applying nursing professional score also as an input in adjustment of education curriculum and supporting professionalism.